Hubungan Dukungan Sosial Suami Dan Motivasi Dengan Mobilisasi Dini Ibu Post Seksio Sesarea Di Ruangan Kasuari Rsu Anutapura Palu - Lastri Gintoe, Hermin; Mulia Sakti, Putri (Jurnal Bidan Cendrawasih Palu, 2019)
The aim of this study is to analyze the correlation between social support of husband of post cesarean section patient with her motivation to had an early mobilization. The population of this study were all post cesarean section patients of Kasuari Ward of Anutapura General Hospital of Palu between March-May 2014. Selected samples were 49 patients which collected using purposive sampling technique. This study was an analytic kind of study. This study was using questionnaires as research tool to collect main data in order to measuring the variables which were social support of patients’ husband, patients’ motivation and early mobilization. The questionnaires used were already valid and reliable. According to results analysis using pearson product moment technique, we found correlation coefficient between social support with early mobilization was (r) = 0.069 with (p) = 0.638 (p>0.05), which means that there is no significant correlation between social support of patients’ husband with her post cesarean section mobilization in Kausari Ward of Anutapura General Hospital of Palu. Otherwise, the correlation coefficent between patients’ motivation with her early mobilization was (r)= 0.688 with (p) = 0.000 (p<0.05) which means there is a significant correlation between patients’ motivation with her decision to did early mobilization of post caesarean section patients in Kasuari Ward of Anutapura General Hospital of Palu. Thus, health providers need to provide nformation about the importance of early mobilization for post caesarian women to improve their motivation in peracticing early mobilization.